The Influence of Innovation on SMEs Business Performance in the Manufacturing Sector - Yusrinadini Zahirah Yusuff; Nur Yuhainis Ab Wahab; Rusnifaezah Musa; Rushanim Hashim (International Journal of Supply Chain Management, 2020)
Nowadays, small and medium-sized enterprises (SMEs) play an important role in contributing to the country's economic growth. Overall, the contribution of SMEs to the Gross Domestic Product (GDP) are increased year by year. However, there are few studies showed that SMEs business performance are still inconsistent and need improvement. Therefore, the Malaysian government through the budget of 2016, has been working to ensure business sustainability, and also support the development and long-term growth of the SMEs. This study aims to investigate the relationship between innovation and business performance among SMEs in Malaysia. A sample of 155 SMEs data has successfully collected through a survey. The collected data was analysed by using the Multiple Regression Analysis. The findings revealed that innovation had a significant positive effect on the SMEs firm business performance.  The findings has strengthen the theory of resource-based view (RBV) by filling in the scarcity of research on innovation as well as contributed to the significance of this study.